CONSUMERS’ ATTITUDE TOWARDS AGRICULTURE PRODUCTS PURCHASED VIA E-COMMERCE PLATFORMS IN SELANGOR - Nur Hazwani Mohammad Azam; Nur Fatin Munirah Aris; Nur Erni Syaliza Ahaddon; Fazleen Abdul Fatah; Abdul Rahman Saili (International Journal of Accounting, Finance and Business, 2022)
The study was conducted to understand consumer perspectives and acceptance ofagriculture products purchased via e-commerce platforms. Three main factors that influenceconsumer perspective were identified which include perceived risk, consumer trust, andperceived benefit. The results showed that, out of three factors, only two significantly influenceattitude towards purchase: perceived benefit and consumer trust. Consequently, attitudesignificantly influences consumer behaviour in purchasing agriculture products via ecommerceplatforms.